Bibliotheken in der NS-Zeit Provenienzforschung und Bibliotheksgeschichte - Alker-Windbichler, Stefan; Köstner-Pemsel, Christina; Stumpf, Markus (2019)
The fate of cultural property extracted during the Nazi era has increasingly been the subject of provenance research since the 1990s. This volume combines the latest findings of provenance research in libraries and provides contributions to the history of the library during the Nazi era. Provenance research is almost only reported in the media when it concerns valuable works of art. For books, it is relatively difficult: it is mostly about mass-produced goods without great material value and the books have often reached their locations after hard-to-find odysseys. Nevertheless, more and more libraries deal with their Nazi past. Library historian Jürgen Babendreier puts it in a nutshell: "In the robbed books, history comes to life, invisible remembrance continues, historical responsibility becomes present."